Prevalence of hypertension and associated factors in males: a cross sectional study in Prayagraj District, Uttar Pradesh - Divakar, Singh Lal; Prakash, Shiv; Parveen, Khurshid; Singh, Richa (International Journal Of Community Medicine And Public Health, 2020)
Background: A disorder that has no apparent symptoms but later results in serious health problems can pose great threat to the health of people. Hypertension is such a major non communicable disease (NCD) and affects about 20% of the population in most communities. Hypertension has a major hand in causation of coronary artery diseases, stroke and various other vascular complications, and renal disorders. The study was done with objective to assess prevalence of hypertension of male which were ≥30 years in Urban and Rural Prayagraj. Methods: A community based cross-sectional study was carried out in Prayagraj District. Study participants were 620 males, 310 urban and 310 rural of age equal or above 30 years and study sampling technique were two stage random sampling. The data was collected by using predesigned, pretested, semi structured questionnaire and analyzed by using SPSS 23.0 version. Results: Prevalence of hypertension was 41.13%. A statistically significant association of hypertension was found with hypertension and BMI, lifestyle, salt consumption, dietary preference and amount of vegetable/fruit each. Conclusions: A high prevalence was found in this study when compared with others study. BMI, lifestyle, salt consumption, dietary preference and amount of vegetable were found to be significantly association risk factors for hypertension among males in Allahabad district.